PJOK Learning Model On Pencak Silat Material: Literatur Review - Heni Yuli Handayani; Septyaningrum Putri Purwoto; Agus Himawan (UNIB Press, 2021)
The learning process that has been going on so far for PJOK teachers in classroom management still tends to be centered on the teacher as the main learning resource (teacher centre). In the physical education learning process, there are various sports that can be used as a means to improve students' psychomotor aspects. One of them is pencak silat. Learning material for Pencak Silat is still limited to direct teacher demonstrations or models. Therefore, an appropriate learning model is needed to be applied in the learning of pencak silat material. Learning models in the pencak silat material include project based learning (PBL) learning models assisted by picture cards, multimedia learning models, move color learning models, jigsaw cooperative learning, NHT type cooperative learning models, and also direct instruction learning models.